PERBANDINGAN KONSTRUKSI PEMBERITAAN KASUS KAUS BOM ATOM BTS DALAM MEDIA MASSA JEPANG ASAHI.COM DAN MAINICHI.JP - Adis Kusumawati (Japanology: The Journal of Japanese Studies, 2019)
A popular boy group from South Korea BTS was being criticized because one of the member once wore a t-shirt with words and image graphic desgin that considered hurting the atomic bomb victims' feeling. This controversy lead to a performance cancellation of theirs in a music broadcast "Music Station” aired by Asahi TV. This case gained attention from many countries especially Japan mass media. In this research, the writer uses news articles that published on November 9 to 10 2018 by online media Asahi.com and Mainichi.jp. This study applies qualitative research method approach and use discourse analysis proposed by Teun A. Van Dijk on the text dimension to determine the atomic bomb t-shirt related news being constructed by both newspapers. The result is there are some difference points between Asahi.com and Mainichi.jp in news constuction.